2010
DOI: 10.1080/00036840802112497
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of DEA efficiency analysis: a bootstrap application to the health care foodservice industry

Abstract: This article analyses the efficiency of health care foodservice operations and its determinants using a Data Envelopment Analysis (DEA) bootstrapping approach. The purpose of using the bootstrapping approach is two-fold: first, to obtain the bias corrected estimates and the confidence intervals of DEA-efficiency scores and second, to overcome the correlation problem of DEA-efficiency scores and to provide consistent inferences in explaining the determinants of health care foodservice efficiency. The approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Simar and Wilson () presented a solution for the latter problem, namely the bootstrapping approach for DEA. The underlying idea is to estimate the population distribution of DEA efficiency scores, thus making it possible to perform hypothesis testing on the efficiency scores (Assaf and Matawie, ).…”
Section: Preliminaries For Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Simar and Wilson () presented a solution for the latter problem, namely the bootstrapping approach for DEA. The underlying idea is to estimate the population distribution of DEA efficiency scores, thus making it possible to perform hypothesis testing on the efficiency scores (Assaf and Matawie, ).…”
Section: Preliminaries For Benchmarkingmentioning
confidence: 99%
“…Bootstrapped DEA was introduced by Simar and Wilson (, , ). Assaf and Matawie () employed bootstrapped DEA to assess the efficiency of health care foodservice facilities. Aldea and Ciobanu () and Aldea et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, regression analysis cannot be robust with this multicollinearity problem. For this reason, a double bootstrapping technique can better reveal the impact of exogenous and operational variables on efficiency scores [10,64]. However, Banker and Natarajan [65] demonstrated that two-stage DEA with ordinary least squares or Tobit outperforms one-stage parametric methods, such as translog and Cobb-Douglas, in defining the production frontier.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the efficiency results in biascorrected is definitely influenced by the error portion discarded. Assaf and Matawie [28] noted that due to the upward-bias in the original estimates and the bootstrap correction in the confidence interval (95%), the original estimates lie to outside for every observation, but can close to the lower bound for the confidence interval. However, the bias corrected estimates lie inside for each observation within the confidence interval.…”
Section: B Efficiency Estimated Bias-corrected Analysis Based On Bdementioning
confidence: 96%